Pyrocumulonimbus lightning and fire ignition on Black Saturday in southeast Australia. Issue 14 (20th July 2017) - Dowdy, Andrew J.; Fromm, Michael D.; McCarthy, Nicholas
Abstract: A number of devastating wildfires occurred in southeast Australia on 7 February 2009, colloquially known as Black Saturday. Atmospheric responses to this extreme fire event are investigated here with a focus on convective processes associated with fire activity (i.e., pyroconvection). We examine six different fire complexes on Black Saturday, finding three clearly distinct pyrocumulonimbus storms, the largest of which reached heights of 15 km on that day and generated hundreds of lightning strokes. The first lightning stroke was recorded near the largest fire complex 5 h after fire ignition. One of the pyrocumulonimbus storms was initiated close to midnight due to mesoscale influences, consistent with extreme fire behavior observed at that time for that particular fire. As another example of fire‐atmosphere interactions, a fire that started late on Black Saturday is examined in relation to ignition caused by pyrogenic lightning, with implications for understanding the maximum rate of spread of a wildfire. Results are discussed in relation to another pyrocumulonimbus event associated with the 2003 Canberra fires. Our findings are intended to provide a greater understanding of pyroconvection and fire‐atmosphere feedback processes, as well as help enhance wildfire response capabilities. We also demonstrate the potential for using lightning, radar, and satellite remote sensing in combination with thermodynamic analyses as well as synoptic and mesoscale dynamics to provide enhanced real‐time guidance for dangerous fire conditions associated with pyroconvection, as well as for the risk of new fire ignitions from pyrogenic lightning. Plain Language Summary: A number of devastating wildfires occurred in southeast Australia on 7 February 2009, colloquially known as Black Saturday. Atmospheric responses to this extreme fire event are investigated here with a focus on convective processes associated with fire activity (i.e., pyroconvection). We show that multiple fire plumes produced a number of distinct pyrocumulonimbus storms, some of which reached heights of 15 km on that day and generated a large amount of lightning. The first lightning stroke was recorded near the largest fire complex 5 h after fire ignition. This offers broad implications for understanding fire behavior exacerbation rates, given that deep convection can produce extreme variations in surface wind conditions. A fire that started late on Black Saturday is examined in relation to ignition caused by pyrogenic lightning, 100 km ahead of the fire front, with implications for understanding extreme fire spread rates. Our findings are intended to provide a greater understanding of pyroconvection and fire‐atmosphere feedback processes, as well as help enhance wildfire response capabilities. We also demonstrate the potential for combining lightning and radar data to provide real‐time guidance for dangerous fire conditions associated with pyroconvection, as well as for the risk of new fire ignitions from pyrogenic lightning. Key Points: Electrified pyrocumulonimbus are investigated for Black Saturday, demonstrating extensive deep convection and lightning activity Relationships between lightning activity and fire behavior are documented, with implications for remote sensing guidance and nowcasting First examination of fire ignition from pyrogenic lightning, indicating extreme distances for the risk of new ignitions